The Effectiveness of Social Welfare Programs in Achieving Social Security for Homelessness in Friendly Schools - Gelil, Esam M. Talat Abdul (European Scientific Journal, ESJ, 2020)
The current paper aims to determine the ability of social welfare programs to achieve social security for homeless children in friendly schools. The study depends on the method of orthodontic study. The study was based on the comprehensive survey of children in the school and they were (50) children, males (n=33) and females(n=17) who were 17 years old. The study findings revealed that children benefit from services provided to them in solving their problems that help them achieve the social stability of the child, through achieving social harmony and helping them to achieve psychological stability for the child, by enhancing his sense ofself-acceptance, tolerance and trust, and achieving material stability for the child. It can be observed that the results of this study assure the validity of the first hypothesis that indicates it was revealed that there is a statistically significant positive relationship between providing social care programs and achieving social stability for homeless children in friendly schools, paying more attention to the needs and problems of homeless children so that they take the largest share of future studies. The researcher proposes the following recommendations: Educating community members about the rights of this group so that they can access the services they need. Future studies are needed to establish mechanisms to implement social welfare programs in a way that ensures the access of displaced children to them, thus achieving social stability and security.